Kualitas Perairan di Selat Makassar Ditinjau dari Aspek Bakteriologi - Djoko Hadi Kunarso (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2011)
Makassar strait is one of the important and strategic straits in Indonesia as it constitutes interislands and international sealanes. Its water condition is under the influence of both Kalimantan and Sulawesi islands, so that the dynamics in the region of marine and coastal environment becomes more complex. A study on water quality of bacteriological points of view in Makassar strait was conducted in October 2003. Seawater and sediment samples were collected by using the Research Vessel Baruna Jaya VIII at 16 stations. The aims of this study is to find out the water quality based on the contents of coliform bcteria and pathogenic bacteria Salmonella and Vibrio. The analysis of coliform bacteria was conducted by using membrane filter technique, while the pathogenic bacteria Salmonella and Vibrio were cultivated in the specific media Selenith broth and TCBS agar. The results showed that coliform bacteria at the surface layers depth varied from 80– 824 CFU/100mL with an average of 245 CFU/100mL, while those at the middle layer varied from 0–60 CFU/100mL with an average of 23 CFU/100mL. Seven pathogenic bacteria were isolated from seawater sample, i.e. Citrobacter spp., Edwardsiella spp., Proteus spp., Pseudomonas spp., Providencia spp., Shigella spp. and Vibrio spp, while eight pathogenic bacteria were obtained at sediment sample, i.e. Aeromonas spp., Citrobacter spp., Proteus spp., Pseudomonas spp., Providencia spp., Shigella spp., Yersenia spp. and Vibrio spp. These results indicated that coliform bacteria content in Makassar strait is under the threshold of Indonesian standard, i.e. Ministry Decree of Environment No: 51, 2004. Vibrio spp. was the pathogenic bacteria found both from seawater and sediment samples. In general, however, pathogenic bacteria was dominated by low pathogenic bacteria. Therefore, it can be concluded that from bacteriological point of view, water quality of Makassar strait is still relatively good.